The Incidence of Precipitation and the Area Sown Against Rice Production in the Department of Meta (Revista "Boletín el Conuco", 2021)
The objective of this article is to analyze the relationship of the impact of precipitation and theamount of area sown against rice production inthe Meta department. For this analysis were obtained precipitation data provided by the IDEAMand data of sown area and production of riceobtained from the information annexed to theIV national census rice of the year 2016, carriedout by the Convention FEDEARROZ-DANE.The values that were analyzed from these threevariables were from the semiannual periods between (1999 -2017). In the case of precipitation,the average was found using the total semestermeasurements of the Pluviometric stations located at the target. After the analysis, it was obtained as results that the production of rice is avariable dependent on the amount of area thatis sown and of the quota Pluviometric as valueadded, ie, the greater amount of sown area and agood rainfall in the cycle Productive, the greaterthe rice production will be.
Keywords: Pluviometric precipitation, rice production, planting area, regression, incidence.